Exploitation of static and dynamic methods for the analysis of the mechanical nanoproperties of polymethylmetacrylate by indentation (Fracture and Structural Integrity, 2021)
The development of instrumented nanoindentation consists of non-destructive tests applied to miniature volumes of material (PMMA). The present research focuses on the factors explaining the variation in the trends of the mechanical properties studied. The evolution of Young's modulus (E) and contact hardness (H) with depth (h) and indentation force (P) shows the existence of an inflection point (2.77 nm) at low penetrations which separates two zones with the first increasing trend and the second decreasing. Explained respectively by the surface hardening induced by the preparation of the material surface and the existence of a surface hardness gradient denoted by the indentation size effect (ISE) observed at very low depths. In addition, on detection of a critical penetration depth below which the effect of the surface on the nanohardness dominates, the variation in the penetration charge is of the order of 9.71 nm. The differences in results of E and H between the dynamic and static modes are of the order of 8.46% and 6.44% inducing an overestimation of 35 MPa in value of E and an underestimation of 1.23 MPa in value of H. They tend to affect the expected nanoscale precision of the indentation to determine the nanomechanical properties of PMMA.
Keywords: Modulus; Hardness; Nanometer scale; Low indentation depths; Indentation size effect